IMPLEMENTATION OF READ ALOUD STRATEGY IN INCREASING CHILDREN'S INTEREST IN READING (Case Study at Aisyiyah Kindergarten, Limapuluh Kota Regency) - Yulianto, Joni; Primadesi, Yona (Departemen Informasi Perpustakaan dan Kearasipan, 2024)
This research aims to describe read aloud strategies in increasing children's interest in reading, both at home and at school. This research uses a qualitative approach with descriptive methods. The results of this research show three main findings: (1) the implementation of the read aloud strategy in increasing children's interest in reading involves the stages of preparation, implementation and evaluation of the activity; (2) factors inhibiting read aloud practice in increasing children's interest in reading, both at school and at home, consisting of internal factors originating from teachers, parents and students themselves as well as external factors including the environment and children's learning media; and (3) the impact of implementing the read aloud strategy in increasing children's interest in reading, which not only succeeded in enriching their vocabulary but also aroused imagination and curiosity. Based on these three findings, it can be concluded that the application of read aloud effectively helps children understand story lines, language structures and new concepts more easily, thus making a positive contribution in increasing their interest in reading.